A / M / X crystal material, photovoltaic device and method for producing the same
By optimizing crystal grain arrangement and surface flatness in perovskite photovoltaic devices with A/M/X crystalline materials and using surfactants and amino compounds, the energy conversion efficiency is enhanced to 21.1%, addressing the inefficiencies in existing devices.
Patent Information
- Application Number
- JP2024536231
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-12-23
- Publication Date
- 2025-01-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing perovskite photovoltaic devices face challenges in achieving high energy conversion efficiency due to suboptimal crystal grain arrangements and surface flatness, which affect light absorption and utilization.
The development of a photovoltaic device with a photoactive crystalline material layer comprising penetrating crystal grains occupying at least 80% of the total grains, and a backlight side with an average flatness coefficient of 75 or less, utilizing A/M/X crystalline materials and a specific manufacturing method involving surfactants and amino compounds.
This configuration significantly enhances the energy conversion efficiency of the photovoltaic device by improving light absorption and utilization, with a synergistic effect from surfactants and amino compounds, resulting in efficiencies up to 21.1% compared to 18.9% without these enhancements.
Smart Images

Figure 2025500920000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of photovoltaics, and in particular to A / M / X crystalline materials, photovoltaic devices and methods for fabricating the same. [Background technology]
[0002] A perovskite photovoltaic device is a photovoltaic device that performs photoelectric conversion using a photoactive perovskite structure material as a photoactive crystalline material layer.
[0003] A typical photoactive perovskite structure material is an organometal halide, which has the general formula AMX3 and is generally an octahedral or cubic structure. In a typical perovskite crystal, the A ion is located at the center of a cubic unit cell and surrounded by 12 X ions to form a coordinated cuboctahedron, forming a three-dimensional periodic structure, and the M ion is located at the vertex of the cubic unit cell and is coordinated around it by 6 X ions to form an octahedral symmetry structure.
[0004] When photoactive perovskite-based materials are irradiated with light, they generate two types of carriers, i.e., electrons and holes, which are then collected by two electrodes to generate photoinduced current. The properties of the perovskite-based structure are an important factor in determining the power conversion efficiency (PCE) of photovoltaic devices. Summary of the Invention
[0005] It is an object of the present application to provide a photovoltaic device with higher energy conversion efficiency.
[0006] A first aspect of the present application provides a photovoltaic device, the device comprising a layer of photoactive crystalline material, the layer of photoactive crystalline material comprising a first region; In the first region, the photoactive crystalline material layer includes through grains, the through grains being grains that penetrate the photoactive crystalline material layer, the number of the through grains being a percentage p≧80%, optionally p≧90%, of the total number of grains in the first region of the photoactive crystalline material layer; and In the first region, the photoactive crystalline material layer includes a backlight side and backlight crystal grains, the backlight crystal grains are crystal grains having at least one surface exposed to the backlight side, and the surface of the backlight crystal grains exposed to the backlight side is a backlight crystal surface; Here, the backlight side has an average flatness coefficient R avg R avg ≦75, optionally 10≦R avg ≦70, Here, R on the backlight side avg is calculated by the following formula:
number
[0007] The photovoltaic device according to the above solution has improved energy conversion efficiency.
[0008] In some embodiments, the photoactive crystalline material comprises an A / M / X crystalline material, the A / M / X crystalline material having the general formula: [A] a [M] b [X] c [M] comprises one or more first cations, the first cations comprising a metal ion, a metalloid ion, or a combination thereof; [A] contains one or more second cations, [X] contains one or more halogen anions, a is 1-6, optionally a is 1, 2, 3, 4, 5 or 6; b is 1-6, optionally b is 1, 2, 3, 4, 5 or 6; c is 1 to 18; optionally, c is 3, 6, 9, or 18.
[0009] The photovoltaic device according to the above solution has improved energy conversion efficiency.
[0010] In some embodiments, the one or more first cations are Ca 2+ , Sr 2+ , Cd 2+ , Cu 2+ , Ni 2+ , Mn 2+、 Fe 2+ , Co 2+ , Pd 2+ , Ge 2+ , Sn 2+、 Pb 2+ , Yb 2+ ,EU 2+ , Bi3+, Sb3+, Pd 4+ , W 4+ , Re 4+ , Os 4+ , Ir 4+ , Pt 4+ , Sn 4+ , Pb 4+ , Ge 4+ or Te 4+ is selected from Optionally, the one or more first cations are Cu2+ , Pb 2+ , Ge 2+ Or Sn 2+ is selected from.
[0011] (2) The one or more second cations are Cs + , (NR 1 R 2 R 3 R 4 ) + , (R 1 R 2 N=CR 3 R 4 ) + , (R 1 R 2 NC(R 5 )=NR 3 R 4 ) + Or (R 1 R 2 NC(NR 5 R 6 )=R 3 R 4 ) + where R 1 , R 2 , R 3 , R 4 , R 5 and R 6 each independently represents H, substituted or unsubstituted C 1-20 is selected from an alkyl group, or a substituted or unsubstituted aryl group; Optionally, the one or more second cations are Cs + , (CH3NH3) + , (H2N-C(H)=NH2) + is selected from.
[0012] (3) The halogen anion is Cl - , Br - or I - is selected from.
[0013] The photovoltaic device according to the above solution has improved energy conversion efficiency.
[0014] In some embodiments, the A / M / X crystalline material is FAPbI3, FAPbBr3, FAPbCl3, FAPbF3, FAPbBr x I 3-x , FAPbBr x Cl 3-x , FAPbI x Br 3-x , FAPbI x Cl 3-x , FAPbCl x Br 3-x , FAPbI 3-x Cl x , CsPbI3, CsPbBr3, CsPbCl3, CsPbF3, CsPbBr x I 3-x , CsPbBr x Cl 3-x , CsPbI x Br 3-x , CsPbI x Cl 3-x , CsPbCl x Br 3-x , CsPbI 3-x Cl x , F.A. 1-y Cs y PbI3, FA 1-y Cs y PbBr3, FA 1-y Cs y PbCl3, FA 1-y Cs y PbF3, FA 1-y Cs y PbBr x I 3-x , F.A. 1-y Cs y PbBr x Cl 3-x , F.A. 1-y Cs y PbI x Br 3-x , F.A. 1-y Cs y PbI x Cl 3-x , F.A. 1-y Cs y PbCl x Br 3-x , F.A. 1-y Cs y PbI3-x Cl x or a combination thereof, Here, x = 0 to 3 and y = 0.01 to 0.25.
[0015] The photovoltaic device according to the above solution has improved energy conversion efficiency.
[0016] In some embodiments, the A / M / X crystalline material is selected from the group consisting of FAPbI3, CsPbI3, FA 1-y Cs y PbI3, or a combination thereof, where y=0.01 to 0.25.
[0017] The photovoltaic device according to the above solution has improved energy conversion efficiency.
[0018] In some embodiments, the thickness of the photoactive crystalline material layer is greater than or equal to 100 nm, optionally between 100 nm and 1000 nm, optionally between 300 nm and 700 nm.
[0019] The photovoltaic device according to the above solution has improved energy conversion efficiency.
[0020] In some embodiments, the photovoltaic device further comprises a first charge transport layer and a second charge transport layer, the photoactive crystalline material layer being located between the first charge transport layer and the second charge transport layer; the first and second charge transport layers are electron transport layers and hole transport layers, respectively; or The first and second charge transport layers are a hole transport layer and an electron transport layer, respectively.
[0021] In some embodiments, the photovoltaic device further comprises a first electrode and a second electrode, the electron transport layer, the hole transport layer and the photoactive crystalline material layer being located between the first electrode and the second electrode; Optionally, the first electrode comprises a transparent conductive oxide; Optionally, the second electrode comprises a metal.
[0022] The photovoltaic device according to the above solution has improved energy conversion efficiency.
[0023] A second aspect of the present application provides a method for producing an A / M / X crystalline material, said A / M / X crystalline material having the general formula: [A] a [M] b [X] c [M] comprises one or more first cations, the first cations comprising a metal ion, a metalloid ion, or a combination thereof; [A] contains one or more second cations, [X] contains one or more halogen anions, a is 1 to 6, for example, a=1; b is 1 to 6, for example, b=1; c is 1 to 18, for example, c=3; The method includes disposing a precursor composition on a substrate, the precursor composition comprising: (a) at least one precursor compound; (b) a solvent, (c) surfactants, and (d) Contains amino compounds.
[0024] When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0025] In some embodiments, the surfactant comprises an amphoteric surfactant.When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0026] In some embodiments, the amino compound includes a nitrile amine-based compound, an amino acid-based compound (e.g., a sulfamic acid-based compound), a hydrazine-based compound, a urea-based compound (e.g., urea, urea formaldehyde, biuret, triuret), a guanidine-based compound, or a salt or hydrate thereof. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0027] In some embodiments, the surfactant comprises dodecylaminopropionate, dodecylethoxysulfobetaine, dodecyldimethylhydroxypropylsulfobetaine, zwitterionic polyacrylamide, octadecyldihydroxyethylamine oxide, tetradecyldihydroxyethylamine oxide, lauramidopropylamine oxide, dodecylbetaine, L-α-phosphatidylcholine, 3-(N,N-dimethyltetradecylammonium)propanesulfonate, dodecylbenzenesulfonate, or combinations thereof. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0028] In some embodiments, the amino compound is urea formaldehyde (C3H8N2O3), isobutyraldehyde condensed urea (C6H 14 N4O2), hydrazine (H4N2), guanidine (CH3N3O), nitrile amine (CH2N2), sulfamic acid (H3NO3S), or a combination thereof. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0029] In some embodiments, the precursor composition includes a first solvent and a second solvent, the first solvent having a boiling point of 40° C. to 165° C., and the second solvent having a boiling point of 170° C. to 250° C. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0030] In some embodiments, the first solvent is selected from one or more of N,N-dimethylformamide (DMF), 2-methoxyethanol, and acetonitrile (ACN).When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0031] In some embodiments, the second solvent is selected from one or more of dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), and diphenyl sulfoxide (DPSO).When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0032] In some embodiments, the volume ratio of the first solvent to the second solvent is (4-10): 1. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0033] In some embodiments, the precursor composition comprises: a first precursor compound containing a first cation; and a second precursor compound containing a second cation.
[0034] When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0035] In some embodiments, the first precursor compound contains a halogen anion. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0036] In some embodiments, the second precursor compound contains a halogen anion.When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0037] In some embodiments, the first precursor compound comprises lead iodide (PbI2), lead bromide (PbBr2), or a combination thereof; In some embodiments, the second precursor compound comprises formamidine hydroiodide (FAI), formamidine hydrobromide (FABr), cesium iodide (CsI), cesium bromide (CsBr), or a combination thereof.
[0038] When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0039] In some embodiments, the method for producing the A / M / X crystalline material further comprises performing a curing process on the precursor composition disposed on the surface of the substrate; Optionally, the curing treatment comprises vacuum treatment, air blading, infrared light treatment, or a combination thereof.When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0040] In some embodiments, the method of producing the A / M / X crystalline material further comprises subjecting the hardened product to an annealing treatment; Optionally, the temperature of the annealing treatment is 100° C. to 170° C.; Optionally, the annealing time is from 5 minutes to 60 minutes.
[0041] When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device exhibits improved energy conversion efficiency.
[0042] A third aspect of the present application provides a method of manufacturing a photovoltaic device, the photovoltaic device including a first electrode, a second electrode, a first charge transport layer and a second charge transport layer located between the first electrode and the second electrode, and an A / M / X crystalline material layer located between the first charge transport layer and the second charge transport layer; The method comprises: providing a first electrode having a first charge transport layer disposed on a surface thereof; forming a layer of the A / M / X crystalline material on a surface of the first charge transport layer according to the method for producing the A / M / X crystalline material described in any one of the above; forming a second charge transport layer over the layer of A / M / X crystalline material; forming a second electrode on the second charge transport layer; wherein the first charge transport layer and the second charge transport layer are an electron transport layer and a hole transport layer, respectively; or The first and second charge transport layers are a hole transport layer and an electron transport layer, respectively.
[0043] The photovoltaic device manufactured according to the above method has improved energy conversion efficiency.
[0044] One or more technical solutions of the present application exhibit one or more of the following beneficial effects:
[0045] (1) Photovoltaic devices show significantly improved power conversion efficiency (PCE), (2) the layer of photoactive crystalline material has a high threading grain fraction p; (3) The photoactive crystalline material layer has a low average flatness coefficient R avg having (4) the surfactant and the nitrogen-containing compound have an unexpected synergistic effect in the method of producing the photoactive crystal layer; (5) The manufacturing method is low cost, efficient, and amenable to scale-up. [Brief description of the drawings]
[0046] [Figure 1] FIG. 1 is a schematic diagram of a photovoltaic device according to some embodiments of the present application. [Diagram 2] 1 is a schematic diagram of a photoactive crystalline material layer of some embodiments of the present application. [Diagram 3] 1(a) and (b) are schematic diagrams of photoactive crystalline material layers according to some embodiments and comparative embodiments of the present application, respectively. [Figure 4] 1 is a scanning electron micrograph of an intermediate product containing a photoactive crystalline material layer of some examples of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0047] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the A / M / X crystal material, photovoltaic device, and manufacturing method thereof of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0048] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. It is noted that if 1 and 2 are listed as the minimum range values, and 3, 4, and 5 are listed as the maximum range values, then the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, a numerical range "a-b" represents a shorthand representation of any combination of real numbers a-b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed herein, and "0-5" is just a shorthand for combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0049] Unless otherwise stated, all the embodiments and optional embodiments in the present application can be combined with each other to form a new technical solution.
[0050] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0051] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, e.g., sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed in sequence, or steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c), which means that step (c) may be added to the method in any order, e.g., the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0052] Unless otherwise specified, the terms "comprise" and "comprise" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprise" may further include or include other ingredients not listed, or may include or include only the listed ingredients.
[0053] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied in the following cases: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) but B is true (or exists); and A and B are both true (or exist).
[0054] [Photovoltaic power generation devices] A photovoltaic device (also called a solar panel or solar cell) is a device for converting solar energy into electrical energy.
[0055] 1 is a schematic diagram of a photovoltaic device according to some embodiments of the present application; and FIG 2 is a schematic diagram of a photoactive crystalline material layer according to some embodiments of the present application.
[0056] 1-2 , in some embodiments, the present application provides a photovoltaic device, the device including a photoactive crystalline material layer 103, the photoactive crystalline material layer 103 including a first region, In the first region, the photoactive crystal material layer 103 includes penetrating crystals 313, the penetrating crystals 313 being crystals that penetrate the photoactive crystal material layer 103, and the ratio p of the number of the penetrating crystals 313 to the total number of crystals in the first region of the photoactive crystal material layer 103 is 80% or more, optionally p 90% or more, optionally p 95% or more, optionally p 99% or more, optionally p=100%; and In the first region, the photoactive crystal material layer 103 includes a backlight side 113 and backlight crystals (31, 32, 33), at least one surface of the backlight crystals (31, 32, 33) is exposed to the backlight side 113, and the surface of the backlight crystals (31, 32, 33) exposed to the backlight side 113 is a backlight crystal face; Here, the backlight side 113 has an average flatness coefficient R avg (Average Flatness Index) and R avg ≦75, optionally 10≦R avg ≦70, and optionally R avg is a value of 1 to 10, 10 to 20, 20 to 30, 30 to 40, 40 to 50, 50 to 60, or 60 to 70; Here, R on the backlight side 113 avg is calculated by the following formula:
number
[0057] In the above solution, the inventor unexpectedly found that by optimizing the shape and arrangement of the crystal grains in the photoactive crystal material layer, the energy conversion efficiency of the photovoltaic device can be significantly improved. Specifically, the inventor found that the ratio p of the number of the through crystal grains 313 in the photoactivated crystal material layer to the total number of crystal grains in the first region of the photoactive crystal material layer 103 is ≧80%, and the average flatness coefficient R avg It has been found that when the ZnO / ZnO content is ≦75, the photovoltaic device exhibits significantly improved power conversion efficiency (PCE).
[0058] Referring to FIG. 2, in some embodiments, the average flatness factor R avg The measurement and calculation method is described in detail in Fig. 2. Fig. 2 shows a crystalline material layer 103, which includes a backlight side 113 and backlight crystal grains (31, 32, 33), the backlight crystal grains (31, 32, 33) are crystal grains exposed to the backlight side 113, and the backlight crystal grains (31, 32, 33) have backlight crystal faces exposed to the backlight side; Here, R on the backlight side 113 avg is calculated by the following formula:
number
[0059] In some embodiments, the value of n is 3 or more, such as 5 or more, such as 10 or more, such as 50 or more, such as 100 or more, such as 500 or more, such as 1000 or more.
[0060] Referring to FIG. 3, (a) and (b) of FIG. 3 respectively show schematic diagrams of two types of photoactive crystalline material layers.
[0061] Referring to FIG. 3(a), a schematic diagram of a first photoactive crystal material layer is shown. As shown in the figure, the number of through-grains 313 of the first photoactive crystal material layer accounts for a ratio p=100% of the total number of grains in the illustrated area of the photoactive crystal material layer 103. The incident light 151 enters the light-receiving surface 112 of the first photoactive crystal material layer, and since the grains of the first photoactive crystal material layer are through-grains 313, the incident light 151 can reach the backlight surface 113 almost without being blocked, so that the first photoactive crystal material layer can be sufficiently irradiated with the incident light 151.
[0062] Referring to FIG. 3(b), a schematic diagram of a comparative photoactive crystalline material layer is shown. As shown in the figure, the crystal grains of the comparative photoactive crystalline material layer are all non-penetrating crystal grains 323, and the ratio p of the number of penetrating crystal grains to the total number of crystal grains in the illustrated area of the photoactive crystalline material layer 103 is 0%. Incident light 151 is incident on the light receiving surface 112 of the comparative photoactive crystalline material layer, and the crystal grains of the comparative photoactive crystalline material layer 313 are all non-penetrating crystal grains 323. Therefore, the incident light 151 is reflected or refracted by the crystal grain boundary 325 before reaching the backlight surface 113, so that the comparative photoactive crystalline material layer cannot fully absorb the radiant energy of the incident light 151.
[0063] The flatness coefficient is a coefficient of the flatness of the surface of the crystal grain. A higher flatness coefficient indicates that the backlight surface of the crystal grain is nearly flat, and a lower flatness coefficient indicates that the crystal grain protrudes more from the backlight surface.
[0064] 3(a), the backlight crystal grains (31, 32, 33) of the first photoactive crystal material layer have a low flatness coefficient (≦75), i.e., the ratio of the width of the backlight crystal grains (31, 32, 33 to the protrusion height (d / h) is low, and the backlight crystal grains (31, 32, 33) have a protruding surface, which allows the backlight side 113 of the comparative photoactive crystal material layer to focus most of the reflected light 152 within the layer, rather than reflecting it out of the layer of the first photoactive crystal material layer, thereby allowing the first photoactive crystal material layer to fully utilize the light energy.
[0065] 3(b), a schematic diagram of a comparative photoactive crystalline material layer is shown, in which the backlight crystal grains (31, 32, 33) of the comparative photoactive crystalline material layer have a high flatness coefficient (>1000), i.e., the backlight crystal grains (31, 32, 33) have a flat backlight crystal surface. The flat backlight surface reflects most of the reflected light 152 out of the layer, so that the comparative photoactive crystalline material layer 312 cannot fully utilize the light energy.
[0066] In some embodiments, the first region refers to a portion or the entire region of the photoactive crystal layer 103 along the layer surface direction.
[0067] In some embodiments, the first region has a dimension in at least one direction of 3 μm or more, such as 10 μm or more, such as 100 μm or more, such as 1 mm or more, such as 1 cm or more, such as 10 cm or more. Optionally, the first region has dimensions in at least two mutually perpendicular directions of 3×3 μm or more, such as 10×10 μm or more, such as 100×100 μm or more, such as 1×1 mm or more, such as 1×1 cm or more, such as 10×10 cm or more, such as 1 m×1 m or more.
[0068] In some embodiments, the total number of crystal grains in the first region of the photoactive crystalline layer is 9 (3×3) or more, such as 16 (4×4) or more, such as 25 (5×5) or more, such as 64 (8×8) or more, such as 100 (10×10) or more, such as 1000 or more.
[0069] In some embodiments, the area of the first region corresponds to 10% or more of the area of the photoactive crystal layer side, such as 50% or more, such as 70% or more, such as 90% or more, such as 100%.
[0070] In some embodiments, the photoactive crystal layer 103 includes a plurality of crystal grains. The crystal grains that penetrate the photoactive crystal material layer 103 are through crystal grains 313. The crystal grains that have at least one surface exposed to the backlight side 113 are backlight crystal grains (31, 32, 33). It should be understood that some crystal grains may belong to the through crystal grains 313 and also to the backlight crystal grains (31, 32, 33). Also, some crystal grains may not belong to the through crystal grains 313 but only to the backlight crystal grains (31, 32, 33).
[0071] In some embodiments, the term "crystalline" refers to a crystalline compound, which is a compound with an extended 3D crystalline structure. Crystalline compounds generally exist in the form of crystals or, in the case of polycrystalline compounds, in the form of microcrystals (i.e., multiple crystals with a grain size of 1 μm or less). The crystals often form layers together. The crystals of a crystalline material may be of any size. When the crystals have dimensions in one or more dimensions in the range of 1 nm to 1000 nm, they may be referred to as nanocrystals.
[0072] In some embodiments, the term "layer" refers to any structure that is essentially laminar (e.g., stretches essentially in two perpendicular directions, but is limited in stretching in a third perpendicular direction). A layer may have a thickness that varies within the extent of the layer. Generally, a layer has a thickness that is approximately constant. The "thickness" of a layer as used herein refers to the average thickness of the layer. The thickness of a layer can be easily measured, for example, using microscopy, such as electron microscopy of a film cross-section, or using surface profilometry, such as a stylus profilometer.
[0073] In some embodiments, the term "light receiving surface" refers to the surface that faces the light source when the photovoltaic device is in operation, and the term "backlight surface" refers to the surface that faces away from the light source when the photovoltaic device is in operation.
[0074] In some embodiments, the term "grain" as used herein refers to a "single crystal grain." For example, one grain refers to one single crystal grain, and the number of grains refers to the number of single crystal grains. The term "single crystal" may be defined as "a single crystal body of crystalline material that contains no large-angle boundaries or twin boundaries" as described in ASTM F1241.
[0075] In some implementations, the term "through" means from one side of the photoactive crystalline layer to the other, for example from the light receiving side to the backlight side.
[0076] In some implementations, the protrusion height of the backlight crystal face is obtained by observing and measuring a micrograph of a cross-section of the photoactive crystal material layer, where the height to which the contour of the backlight crystal face protrudes relative to a reference plane of the backlight face in the micrograph of the cross-section is defined as the protrusion height of the backlight crystal face, and the width to which the contour of the backlight crystal face protrudes relative to the reference plane of the backlight face is defined as the width of the backlight crystal face. The reference plane of the backlight face refers to a continuous, substantially flat surface that passes through approximately the lowest point of each backlight crystal face.
[0077] In some embodiments, the photoactive crystalline material comprises an A / M / X crystalline material, the A / M / X crystalline material having the general formula: [A] a [M] b [X] c [M] comprises one or more first cations, the first cations comprising a metal ion, a metalloid ion, or a combination thereof; [A] contains one or more second cations, [X] contains one or more halogen anions, a is 1-6, optionally a is 1, 2, 3, 4, 5 or 6; b is 1-6, optionally b is 1, 2, 3, 4, 5 or 6; c is 1 to 18, and optionally c is 3, 6, 9, or 18. Based on the above scheme, the photovoltaic device has improved energy conversion efficiency.
[0078] In some embodiments, the one or more first cations are Ca 2+ , Sr 2+ , Cd 2+ , Cu 2+ , Ni 2+ , Mn 2+、 Fe 2+ , Co 2+ , Pd 2+ , Ge 2+ , Sn 2+、 Pb 2+ , Yb 2+ ,EU 2+ , Bi3+, Sb3+, Pd 4+ , W 4+ , Re 4+ , Os 4+ , Ir 4+ , Pt 4+ , Sn 4+ , Pb 4+ , Ge 4+ or Te 4+ According to the above solution, the photovoltaic device has improved energy conversion efficiency.
[0079] In some embodiments, the one or more first cations are Cu 2+ , Pb 2+ , Ge 2+ Or Sn 2+ According to the above solution, the photovoltaic device has improved energy conversion efficiency.
[0080] In some embodiments, the one or more second cations are Cs + , (NR 1 R 2 R 3 R4 ) + , (R 1 R 2 N=CR 3 R 4 ) + , (R 1 R 2 NC(R 5 )=NR 3 R 4 ) + Or (R 1 R 2 NC(NR 5 R 6 )=R 3 R 4 ) + where R 1 ,R 2 ,R 3 ,R 4 ,R 5 and R 6 each independently represents H, substituted or unsubstituted C 1-20 The alkyl group may be selected from the group consisting of an alkyl group, a substituted or unsubstituted aryl group, etc. Based on the above solution, the photovoltaic device has improved energy conversion efficiency.
[0081] In some embodiments, the one or more second cations are Cs + , (CH3NH3) + , (H2N-C(H)=NH2) + According to the above solution, the photovoltaic device has improved energy conversion efficiency.
[0082] In some embodiments, the halogen anion is Cl. - , Br - or I - According to the above solution, the photovoltaic device has improved energy conversion efficiency.
[0083] In some embodiments, the A / M / X crystalline material is FAPbI3, FAPbBr3, FAPbCl3, FAPbF3, FAPbBr x I 3-x , FAPbBrx Cl 3-x 、FAPbI x Br 3-x 、FAPbI x Cl 3-x 、FAPbCl x Br 3-x 、FAPbI 3-x Cl x 、CsPbI3、CsPbBr3、CsPbCl3、CsPbF3、CsPbBr x I 3-x 、CsPbBr x Cl 3-x 、CsPbI x Br 3-x 、CsPbI x Cl 3-x 、CsPbCl x Br 3-x 、CsPbI 3-x Cl x 、FA 1-y Cs y PbI3、FA 1-y Cs y PbBr3、FA 1-y Cs y PbCl3、FA 1-y Cs y PbF3、FA 1-y Cs y PbBr x I 3-x 、FA 1-y Cs y PbBr x Cl 3-x 、FA 1-y Cs y PbI x Br 3-x 、FA 1-y Cs y PbI x Cl 3-x 、FA 1-y Cs y PbCl x Br 3-x 、FA 1-y Cs y PbI 3-x Cl x 2014-05-20 10:00:00 AM | Here, x=0 to 3, and y=0.01 to 0.25. Based on the above scheme, the photovoltaic device has improved energy conversion efficiency.
[0084] In some embodiments, the A / M / X crystalline material is selected from the group consisting of FAPbI3, CsPbI3, FA 1-y Cs y PbI3, or a combination thereof, where y=0.01-0.25. Based on the above scheme, the photovoltaic device has improved energy conversion efficiency.
[0085] In some embodiments, the A / M / X crystalline material is a perovskite material. Optionally, the A / M / X crystalline material is a metal halide perovskite. The term "metal halide perovskite" refers to a perovskite whose formula includes at least one metal cation and at least one halogen anion. Optionally, the A / M / X crystalline material is a mixed halide perovskite. The term "mixed halide perovskite" refers to a perovskite or mixed perovskite that includes at least two types of halogen anions. Optionally, the A / M / X crystalline material is a mixed cation perovskite. The term "mixed cation perovskite" refers to a perovskite that is a mixed perovskite that includes at least two types of A cations. Based on the above solutions, a photovoltaic device has improved energy conversion efficiency.
[0086] In some embodiments, the term "perovskite" refers to a material having a three-dimensional crystal structure related to that of CaTiO3, or includes layer materials having a structure related to that of CaTiO3. A material having a structure related to that of CaTiO3 may be referred to as a perovskite having a "3D perovskite structure" or is called a "3D perovskite". The structure of CaTiO3 can be represented by the formula AMX3, where A and M are cations of different sizes and X is an anion. In the unit cell, the cation A is at the (0,0,0) position, the cation M is at the (1 / 2,1 / 2,1 / 2) position, and the anion X is at the (1 / 2,1 / 2,0) position. The cation A is generally larger than the cation M. As one skilled in the art will appreciate, when A, M and X are varied, the different ion sizes can cause the structure of the perovskite material to be distorted from that of CaTiO3 to a less symmetrical distorted structure. Materials that include layers of perovskite materials are known. For example, the structure of a material that employs a K2NiF4-type structure includes a layer of perovskite material. This is referred to in the art as a "2D layered perovskite" and is structurally distinct from the 3D perovskites described above. A 2D layered perovskite can be represented by the formula [A]2[M][X]4, where [A] is at least one cation, [M] is at least one cation that is different in size from the cation [A], and [X] is at least one anion.
[0087] In some embodiments, the thickness of the photoactive crystalline material layer is greater than or equal to 100 nm, optionally between 100 and 1000 nm, optionally between 300 and 700 nm. Based on the above solutions, photovoltaic devices have improved energy conversion efficiency.
[0088] In some embodiments, the photovoltaic device further comprises a first charge transport layer 104 and a second charge transport layer 102, the photoactive crystalline material layer 103 being located between the first charge transport layer 104 and the second charge transport layer 102; the first charge transport layer 104 and the second charge transport layer 102 are electron transport layers and hole transport layers, respectively; or The first charge transport layer 104 and the second charge transport layer 102 are a hole transport layer and an electron transport layer, respectively. Based on the above solution, the photovoltaic device has improved energy conversion efficiency.
[0089] In some embodiments, the photovoltaic device further comprises a first electrode 105 and a second electrode 101, the electron transport layer, the hole transport layer and the photoactive crystalline material layer being located between the first electrode 105 and the second electrode 101; Optionally, the first electrode 105 comprises a transparent conductive oxide; Optionally, the second electrode 101 comprises a metal. Based on the above solution, the photovoltaic device has improved energy conversion efficiency.
[0090] In some embodiments, the present application further provides a method of making an A / M / X crystalline material, the A / M / X crystalline material having the general formula: [A] a [M] b [X] c [M] comprises one or more first cations, the first cations comprising a metal ion, a metalloid ion, or a combination thereof; [A] contains one or more second cations, [X] contains one or more halogen anions, a is 1 to 6, for example, a=1; b is 1 to 6, for example, b=1; c is an integer from 1 to 18, for example, c=3.
[0091] The method includes disposing a precursor composition on a substrate, the precursor composition comprising: (a) at least one precursor compound; (b) a solvent, (c) surfactants, and (d) Contains ingredients called organic nitrogen-containing compounds.
[0092] In the above solution, the inventors unexpectedly discovered that by using a surfactant in combination with an amino compound to prepare a precursor composition for an A / M / X crystalline material, the prepared A / M / X crystalline material has both a high through-grain ratio and a low flatness coefficient, and when the A / M / X crystalline material is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0093] In some embodiments, the concentration of the at least one precursor compound in the precursor composition is between 0.5 mol / L and 2.5 mol / L, such as between 0.5 mol / L and 1.5 mol / L, such as between 1.5 mol / L and 2.5 mol / L.
[0094] In some embodiments, the concentration of the surfactant in the precursor composition is between 0.05 wt % and 0.5 wt %, such as between 0.1 wt % and 0.2 wt %, between 0.2 wt % and 0.3 wt %, between 0.3 wt % and 0.4 wt %, or between 0.4 wt % and 0.5 wt %.
[0095] In some embodiments, the concentration of the amino compound in the precursor composition is between 1 wt % and 10 wt %, such as between 2 wt % and 4 wt %, between 4 wt % and 6 wt %, between 6 wt % and 8 wt %, or between 8 wt % and 10 wt %.
[0096] In some embodiments, the term "surfactant" refers to any amphiphilic compound (molecule or ion) that contains hydrophilic and lipophilic moieties. Surfactants generally act by accumulating at the oil-water interface, orienting the hydrophilic moiety toward the aqueous phase and the lipophilic moiety toward the hydrophobic phase, thereby reducing the surface tension. Suitable surfactants include water-insoluble surfactants, water-dispersible surfactants, and water-soluble surfactants.
[0097] In some embodiments, the surfactant comprises an amphoteric surfactant.
[0098] The term "amphoteric surfactant" refers to a compound having a cationic and anionic center linked to the same molecule. In particular, the cationic portion is based on a primary, secondary, tertiary or quaternary ammonium cation. The anionic portion includes, but is not limited to, carboxylate, sulfonate and phosphate. More particularly, the "amphoteric surfactant" refers to a compound having a N(O)O-, SO3H or SO3- functional group bonded thereto. + -O-functional group, quaternary N + This refers to compounds that have a tertiary N-functional group linked to a C(O)OH, C(O)O-, SO3H or SO3- functional group.
[0099] For a description of amphoteric surfactants and their properties, reference may be made to Amphoteric Surfactants, 2nd ed., EG Lomax, Ed., 1996, Marcel Dekker Publishers. This class of surfactants includes betaines such as fatty alkyl betaines, fatty alkyl amido betaines, sulfobetaines, hydroxysulfobetaines, and imidazoline-derived betaines, amine oxides such as fatty alkyl amine oxides, fatty alkyl amido amine oxides, amphoteric glycine salts and amphoteric propionates, and the so-called "balanced" amphoteric polycarboxy glycine salts and amphoteric polycarboxy propionates.
[0100] In some embodiments, the amino compound comprises an aminonitrile-based compound, an amino acid-based compound, a hydrazine-based compound, a urea-based compound (e.g., urea, urea formaldehyde, biuret, triuret), a guanidine-based compound, or a salt or hydrate thereof.
[0101] In some embodiments, the term "amino compounds" refers to any compound that contains at least one primary, secondary, tertiary, or quaternary ammonium group.
[0102] In some embodiments, the amino-based compound is a C1-C20 compound, such as a C1-C15 compound, such as a C1-C10 compound, such as a C1-C5 compound, a C15-C20 compound.
[0103] In some embodiments, the term "aminonitrile compounds" refers to compounds that contain at least one "amino-methyl-cyano." Optionally, "aminonitrile compounds" include aminonitrile (AAN), iminodiacetonitrile (IDAN), or ethylenediaminediacetonitrile (EDN).
[0104] In some embodiments, the term "amino acid" refers to a molecule having at least one amino group and at least one carboxy group.
[0105] In some embodiments, the term "sulfamic acid compound" refers to a molecule that contains at least one amino group and at least one sulfo group.
[0106] In some embodiments, the term "hydrazine-based compounds" includes hydrazine and substituted hydrazines.
[0107] In some embodiments, substituted means that the H atoms of the substituted compound are replaced with one or more of alkyl, alkenyl, alkynyl, cycloalkyl, cycloalkenyl, cycloalkynyl, aryl, heteroaryl, and heterocyclic groups.
[0108] In some embodiments, the term "urea-based compound" refers to -NR 1 R 2 -C(=S)-NR 3 R 4 - groups, each R 1 , R 2 , R 3 and R 4is independently selected from H, alkyl groups, alkenyl groups, alkynyl groups, cycloalkyl groups, cycloalkenyl groups, cycloalkynyl groups, aryl groups, heteroaryl groups, and heterocyclic groups. Optionally, the urea-based compounds include urea, thiourea, urea formaldehyde, biuret, triuret, and substituted versions thereof.
[0109] In some embodiments, the surfactant comprises dodecylaminopropionate, dodecylethoxysulfobetaine, dodecyldimethylhydroxypropylsulfobetaine, zwitterionic polyacrylamide, octadecyldihydroxyethylamine oxide, tetradecyldihydroxyethylamine oxide, lauramidopropylamine oxide, dodecylbetaine, L-α-phosphatidylcholine, 3-(N,N-dimethyltetradecylammonium)propanesulfonate, dodecylbenzenesulfonate, or a combination thereof. According to the above method, the photovoltaic device has improved energy conversion efficiency. When the A / M / X crystal material manufactured according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0110] In some embodiments, the surfactant comprises dodecylbetaine, 3-(N,N-dimethyltetradecylammonium)propanesulfonate, lauramidopropylamine oxide, L-α-phosphatidylcholine, or a combination thereof. When the A / M / X crystal material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0111] In some embodiments, the amino-based compound is urea formaldehyde (C3H8N2O3), isobutyraldehyde condensed urea (C6H 14N4O2), hydrazine (H4N2), guanidine (CH3N3O), nitrile amine (CH2N2), sulfamic acid (H3NO3S), or a combination thereof. Based on the above method, a photovoltaic device has improved energy conversion efficiency. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0112] In some embodiments, the amino-based compound comprises guanidine, sulfamic acid, urea, or a combination thereof.When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0113] In some embodiments, the precursor composition includes a first solvent and a second solvent, the boiling point of the first solvent is 40°C to 165°C (e.g., 40°C to 60°C, 60°C to 80°C, 80°C to 100°C, 100°C to 120°C, 120°C to 140°C, or 140°C to 160°C), and the boiling point of the second solvent is 170°C to 250°C (e.g., 170°C to 190°C, 190°C to 210°C, 210°C to 230°C, or 230°C to 250°C). In this solution, the combination of a first solvent with a specific boiling point and a second solvent with a specific boiling point can effectively improve the coverage and crystal quality of the film formed of the A / M / X crystal material.
[0114] In some embodiments, the first solvent is selected from one or more of N,N-dimethylformamide (DMF), 2-methoxyethanol, and acetonitrile (ACN).When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0115] In some embodiments, the second solvent is selected from one or more of dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), and diphenyl sulfoxide (DPSO).When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0116] In some embodiments, the volume ratio of the first solvent to the second solvent is (4-10): 1. By using a combination of a first solvent having a specific boiling point and a second solvent having a specific boiling point in the above specific ratio, the coverage and crystal quality of the film formed of the A / M / X crystal material can be effectively improved.
[0117] In some embodiments, the precursor composition comprises: a first precursor compound containing a first cation; and a second precursor compound containing a second cation. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0118] In some embodiments, the first precursor compound contains a halogen anion. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0119] In some embodiments, the second precursor compound contains a halogen anion.When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0120] In some embodiments, the first precursor compound comprises lead iodide (PbI2), lead bromide (PbBr2), or a combination thereof. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0121] In some embodiments, the second precursor compound comprises formamidine hydroiodide (FAI), formamidine hydrobromide (FABr), cesium iodide (CsI), cesium bromide (CsBr), or a combination thereof. When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0122] In some embodiments, the method for producing the A / M / X crystalline material further comprises performing a curing process on the precursor composition disposed on the surface of the substrate; Optionally, the curing treatment comprises vacuum treatment, air blading, infrared light treatment, or a combination thereof.When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0123] In some embodiments, the method for producing the A / M / X crystalline material further comprises performing an annealing process on the cured product.When the A / M / X crystalline material produced according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0124] In some embodiments, the annealing temperature is 100° C. to 170° C. (e.g., 100° C. to 120° C., 120° C. to 140° C., 140° C. to 160° C., or 160° C. to 170° C.). When the A / M / X crystalline material prepared according to the above methods is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0125] In some embodiments, the annealing time is 5 min to 60 min (e.g., 5 min to 15 min, 15 min to 25 min, 25 min to 35 min, 35 min to 45 min, or 45 min to 55 min).When the A / M / X crystalline material prepared according to the above method is used in a photovoltaic device, the photovoltaic device has improved energy conversion efficiency.
[0126] In some embodiments, the present application further provides a method of manufacturing a photovoltaic device, the photovoltaic device comprising a first electrode 105, a second electrode 101, a first charge transport layer 104 and a second charge transport layer 102 located between the first electrode 105 and the second electrode 101, and an A / M / X crystalline material layer located between the first charge transport layer 104 and the second charge transport layer 102; The method comprises: providing a first electrode 105 having a first charge transport layer 104 disposed on a surface thereof; forming a layer of the A / M / X crystalline material on the surface of the first charge transport layer 104 according to the method for producing the A / M / X crystalline material described in any one of the above; forming a second charge transport layer 102 on the layer of A / M / X crystalline material; forming a second electrode 101 on the second charge transport layer 102; wherein the first charge transport layer 104 and the second charge transport layer 102 are an electron transport layer and a hole transport layer, respectively; or The first charge transport layer 104 and the second charge transport layer 102 are a hole transport layer and an electron transport layer, respectively. A photovoltaic device fabricated according to the above scheme has improved energy conversion efficiency.
[0127] In some embodiments, the photovoltaic device comprises: a first electrode (e.g., comprising a transparent conductive oxide) layer; a first charge transport material layer (e.g. a hole transport material layer); a layer of photoactive crystalline material; a second charge transport material layer (e.g., an electron transport material layer); and a second electrode layer (eg, comprising an elemental metal). Photovoltaic devices fabricated according to the above solutions have improved energy conversion efficiency.
[0128] In some embodiments, the photovoltaic device comprises: a first electrode (e.g., comprising a transparent conductive oxide) layer; a first charge transport material layer (e.g., an electron transport material layer); a layer of photoactive crystalline material; a second charge transport material layer (e.g. a hole transport material layer); and a second electrode layer (eg, comprising an elemental metal). Photovoltaic devices fabricated according to the above solutions have improved energy conversion efficiency.
[0129] [Photoactive crystal material layer] In some embodiments, "photoactive crystalline material" refers to a material that can absorb light and generate free carriers (eg, electrons and holes).
[0130] In some embodiments, the photoactive crystalline material can absorb and / or emit photons, typically in the visible region of the light spectrum, e.g., in the blue region of the visible light spectrum. As such, the photoactive crystalline material may be described as a light-emitting material (i.e., a material that can emit light) or a light-absorbing material (i.e., a material that can absorb light). For example, the photoactive crystalline material can emit and / or absorb at least one type of photon, e.g., having a wavelength between 450 and 700 nm, e.g., between 450 and 650 nm.
[0131] In some embodiments, the photoactive crystalline material may comprise 5 wt% or more of A / M / X crystalline material. For example, the photoactive crystalline material may comprise 80 wt% or more of A / M / X crystalline material, such as 95 wt% or more of A / M / X crystalline material, such as 99 wt% or more of A / M / X crystalline material. The photoactive crystalline material may consist of, or consist essentially of, A / M / X crystalline material.
[0132] In some embodiments, the photoactive crystalline material is, for example, a solid.
[0133] In some embodiments, the photoactive crystalline material layer comprises a film of A / M / X crystalline material. Typically, A / M / X crystalline material is polycrystalline, and accordingly, the photoactive crystalline material comprises a polycrystalline A / M / X crystalline material.
[0134] In some embodiments, the photoactive crystalline material layer may include multiple layers, each of which may include partially or entirely A / M / X crystalline material.
[0135] In some embodiments, the A / M / X crystalline material may be distributed uniformly or non-uniformly throughout the photoactive crystalline material layer. For example, the photoactive crystalline material may include a layer that consists essentially of or consists only of A / M / X crystalline material. Alternatively or additionally, the photoactive crystalline material may include a substrate (e.g., in powder form or in film form) on which the A / M / X crystalline material is disposed.
[0136] [Electron transport layer] In some embodiments, the electron transport layer is a layer that contains an electron transport material (also called an n-type semiconductor material). The electron transport material can be a single electron transport compound or elemental material, or a mixture of two or more electron transport compounds or elemental materials. The electron transport compound or elemental material can be undoped or doped with one or more doping elements.
[0137] Examples of electron transport materials are known to those of skill in the art.
[0138] The electron transport material may include a fullerene or a derivative of a fullerene, such as C60, C70, PCBM, PC71BM, bis[C60]BM (i.e., bis-C60-methyl butyrate), ICBA (CAS: 1207461-57-1).
[0139] The electron transport material may include an organic electron transport material, such as perylene or a derivative thereof, P(NDI2OD-T2) (CAS: 1100243-40~0), or bathocuproine (BCP).
[0140] The electron transport material may include inorganic electron transport materials such as metal oxides, metal sulfides, metal selenides, metal tellurides, perovskites, amorphous silicon, n-type Group IV semiconductors, n-type Group III-V semiconductors, n-type Group II-VI semiconductors, n-type Group I-VII semiconductors, n-type Group IV-VI semiconductors, n-type Group V-VI semiconductors, and n-type Group II-V semiconductors, any one of which may be doped or undoped.
[0141] [Hole transport layer] In some embodiments, a hole transport layer refers to a layer that contains a hole transporting (also called a p-type semiconductor material) material.
[0142] Examples of hole transport materials are known to those skilled in the art. The hole transport material may be a single type of hole transport compound or elemental material, or a mixture of two or more types of hole transport compounds or elemental materials. The hole transport compounds or elemental materials may be undoped or doped with one or more doping elements.
[0143] Organic hole transport materials may include, for example, spiro-OMeTAD, P3HT, PCPDTBT, poly-TPD, spirocycle(TFSI)2 and PVK.
[0144] Inorganic hole transport materials may include oxides of nickel (e.g., NiO), vanadium, copper or molybdenum, CuI, CuBr, CuSCN, CuO, CuO or CIS, perovskites, amorphous silicon, p-type Group IV semiconductors, p-type Group III-V semiconductors, p-type Group II-VI semiconductors, p-type Group I-VII semiconductors, p-type Group IV-VI semiconductors, p-type Group V-VI semiconductors and p-type Group II-V semiconductors, which inorganic materials may be doped or undoped.
[0145] [electrode] The term "electrode" means a region or layer that consists or consists essentially of an electrode material.
[0146] The photovoltaic device of the present application may further include a first electrode and a second electrode.
[0147] The first electrode may comprise a metal (e.g. silver, gold, aluminum or tungsten), an organic conductive material (e.g. PEDOT:PSS), or a transparent conductive oxide (e.g. fluorine doped tin oxide (FTO), aluminum doped zinc oxide (AZO) or indium doped tin oxide (ITO)). Typically, the first electrode is a transparent electrode. Thus, the first electrode typically comprises a transparent conductive oxide, e.g. FTO, ITO or AZO. The thickness of the layer of the first electrode is, for example, 10 nm to 1000 nm, e.g. 40 nm to 400 nm.
[0148] The second electrode may have the same properties as the first electrode, for example, the second electrode may include a metal (e.g., silver, gold, aluminum, or tungsten), an organic conductive material (e.g., PEDOT:PSS), or a transparent conductive oxide (e.g., fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), or indium-doped tin oxide (ITO)). In general, the second electrode includes or consists essentially of a metal (e.g., elemental metal). Examples of materials for the second electrode that may include or consist essentially of a metal include, for example, silver, gold, copper, aluminum, platinum, palladium, or tungsten. The second electrode may be deposited and formed by vacuum evaporation. The thickness of the second electrode material layer is, for example, 10 to 1000 nm, for example, 50 nm to 150 nm.
[0149] [Example] The technical solution of the present application will be described in detail below in conjunction with specific examples and comparative examples. Unless otherwise specified, the reagents, methods and equipment used in the present application are general food-grade reagents, methods and equipment in the art. Unless otherwise specified, the test conditions used in the examples of the present application are general test conditions in the art. Unless otherwise specified, the reagents used in the examples of the present application are all commercially available products.
[0150] The CAS numbers for some raw materials and reagents are as follows:
[0151] [ka]
[0152] Example 1 Referring to FIG. 1, in which the arrow indicates the direction of light irradiation, the photovoltaic device of Example 1 includes a base 106, a first electrode 105, a first charge transport layer 104, a photoactive crystalline material layer 103, a second charge transport layer 102, and a second electrode 101, which are stacked in sequence.
[0153] The method for manufacturing the photovoltaic device of Example 1 is as follows.
[0154] (1) 1362 mg of formamidine hydroiodide (FAI), 228.6 mg of cesium iodide (CsI), and 4056.9 mg of lead iodide (PbI2) are dissolved in 8 mL of solvent to prepare a perovskite precursor solution, where the molar concentration of FAI is 0.99 mol / L, the molar concentration of CsI is 0.11 mol / L, and the molar concentration of PbI2 is 1.1 mol / L. The solvent is a mixture of DMF (N,N-dimethylformamide) and NMP (N-methylpyrrolidone) in a volume ratio of 7:1. Then, a surfactant and a nitrogen-containing compound are further added to the above solvent, and the weight percentages of both are 0.1 wt% and 5 wt%, respectively. In Example 1, the surfactant is dodecyl betaine, and the nitrogen-containing compound is urea.
[0155] (2) Provide a 2 cm×2 cm FTO conductive glass (FTO conductive glass is a glass coated with an FTO conductive layer on its surface, and FTO is an abbreviation of Fluorine doped tin oxide), which includes a glass plate and an FTO conductive layer deposited on the glass plate. Using a laser engraving technique, remove a 0.66 cm wide portion of the FTO conductive layer from two opposite edges of the FTO conductive glass, leaving an FTO conductive layer with a dimension of 2 cm×1.34 cm on the FTO conductive glass, where the glass plate is a base 106 and the FTO conductive layer is a first electrode 105.
[0156] (3) Using magnetron sputtering technology, a first charge transport layer 104 (nickel oxide layer) is formed on the first electrode 105 (FTO conductive layer), and the thickness of the nickel oxide layer is about 20 nm. The first charge transport layer 104 here is a hole transport layer.
[0157] (4) The precursor solution was applied onto the nickel oxide layer, and the sample was transferred to a vacuum chamber and left at a vacuum of 100 Pa for 120 seconds to harden the precursor solution and form a film. The hardened sample was placed on a hot stage and annealed at a temperature of 150°C for 30 minutes. After annealing, a good A / M / X crystal material layer was formed on the nickel oxide layer. In this embodiment, the components of the A / M / X crystal material were FA, ... 0.9 Cs 0.1 The A / M / X crystalline material layer was here designated as the photoactive crystalline material layer 103.
[0158] (6) The sample obtained in the previous step is placed in a deposition system to deposit a second charge transport layer 102 on the photoactive crystalline material layer 103, where the second charge transport layer 102 is an electron transport layer. The second charge transport layer is a 30 nm thick C 60 (fullerene) layer and a BCP (bathocuproine) layer with a thickness of 8 nm.
[0159] (7) Still in the above deposition system, a second electrode 101 was formed on the second charge transport layer 102, where the second electrode 101 was a metallic copper layer with a thickness of 100 nm, and the photovoltaic device of Example 1 was obtained.
[0160] Examples 2 to 4 Examples 2 to 4 differ from Example 1 in that the types of surfactants and / or nitrogen-containing compounds in the precursor solutions are different.
[0161] For more information on the differences between surfactants and nitrogen-containing compounds, see Table 1.
[0162] Comparative Examples 1 to 8 The difference between Comparative Example 1 and Example 1 is that the precursor solution does not contain a surfactant and a nitrogen-containing compound.
[0163] The differences between Comparative Examples 2 to 8 and Example 1 are that the precursor solutions do not contain a surfactant, and that the type or content of the nitrogen-containing compound is different.
[0164] For more information on the differences between surfactants and nitrogen-containing compounds, see Table 1.
[0165] Analysis and Detection 1. Morphological characteristics: (1) Sample preparation: According to the method of Example 4, steps (1) to (4) were carried out, and the product of step (6) was used as the observation sample. A glass cutter was used to make a straight scratch on one side of the glass plate as the observation sample, and the photovoltaic device was split into two along the scratch to expose the cross section.
[0166] (2) Observation of sample: A scanning electron microscope (SEM) is used to observe the cross section and take a picture at a magnification of 30,000 times, as shown in Fig. 4. The observed sample includes a base 106, a first electrode 105 laminated on the base 106, a first charge transport layer 104 laminated on the first electrode 105, and a photoactive crystal material layer 103 laminated on the first charge transport layer 104.
[0167] (3) Crystal morphology of the photoactive crystalline material layer: As shown in FIG. 4, within the area of the photograph, the cross-sectional length of photoactive crystalline material layer 103 is 3.7 μm, and the total number of perfect grains within the area is four.
[0168] First, the photoactive crystal material layer 103 includes penetrating crystal grains 313, which are crystal grains that penetrate the photoactive crystal material layer 103, and the number of penetrating crystal grains 313 is 4, which represents a proportion p=100% of the total number of crystal grains in the illustrated area of the photoactive crystal material layer 103.
[0169] Secondly, the photoactive crystalline material layer 103 includes a backlight side 113 and backlight crystal grains, the backlight crystal grains being crystal grains exposed to the backlight side 113, and the backlight crystal grains having a backlight crystal surface exposed to the backlight side 113; Within the area of the photograph, the backlight side has an average flatness coefficient R avg = 11.4, Here, R in the photo domain avg is calculated by the following formula:
number
[0170] The products of step (6) obtained in Examples 1 to 4 and Comparative Examples 1 to 8 were observed using a scanning electron microscope, and cross sections of the photoactive crystalline material layer with a length of 3.7 μm were collected; (1) the proportion p of the threading grains 313 to the total number of grains in the photographic area of the layer of photoactive crystalline material; (2) Average flatness coefficient R on the backlight side avg The following was calculated:
[0171] The specific results are shown in Table 1.
[0172] 2. Characterization of energy conversion efficiency For the solar power generation devices obtained in the methods of Examples 1 to 4 and Comparative Examples 1 to 8, standard pseudo solar light (AM1.5G, 100 mW / cm 2 The power conversion efficiency (PCE) of the photovoltaic device was tested under irradiation of 1000 nm. For the test method, please refer to the literature Stabilizing perovskite-substrate interfaces for high-performance perovskite modules, Science 373, 902 (2021), and the test results are shown in Table 1.
[0173] [Table 1]
[0174] Analysis and conclusions: (1) About solar power generation devices The energy conversion efficiencies of the solar power generation devices of Examples 1-4 were 20.1%-21.1%, which are significantly higher than the 16%-18.9% of Comparative Examples 1-8.
[0175] The significantly improved energy conversion efficiency of the photovoltaic devices of Examples 1 to 4 is due to the photoactive crystalline layer of the photovoltaic devices simultaneously satisfying the following features a) and b).
[0176] a) the proportion p of the penetrating grains 313 to the total number of grains in the photographic area of the layer of photoactive crystalline material is ≧80, for example even reaching p=100; and b) The backlight side has an average flatness coefficient R avg ≦75, for example R avg =16~59.
[0177] (2) Synergistic effects of surfactants and nitrogen-containing compounds Compared with Comparative Examples 1 to 8, the precursor solutions of Examples 1 to 4 further contain a surfactant and a nitrogen-containing compound in addition to the precursor compound.
[0178] The present application relates to a method for manufacturing a crystal grain having a penetration grain 313 occupancy rate p≧80 and an average flatness coefficient R avg It has been found that it is difficult to obtain a photoactive crystal material layer having an average flatness coefficient R ≦75. As shown in Comparative Examples 1 to 8, when the precursor solution does not contain a surfactant and a nitrogen-containing compound, but contains a surfactant alone, or contains a nitrogen-containing compound alone, the penetration grain 313 occupancy ratio p≧80 and the average flatness coefficient R avg It is not possible to obtain a photoactive crystalline material layer with a refractive index of ≦75, and it is not possible to obtain a photoactive crystalline material layer with improved light absorption properties.
[0179] The present application provides a method for manufacturing a crystal grain having a through grain 313 occupancy rate p≧80 and an average flatness coefficient R avg It has been surprisingly found that layers of photoactive crystalline material of ≦75 nm can be successfully obtained.
[0180] It should be emphasized that the surfactant and the nitrogen-containing compound have a synergistic effect, significantly improving the photoelectric conversion performance of the photoactive crystal material layer. In the last column of Table 1, the increase rate of the photoelectric conversion efficiency of the other comparative examples and Examples 1 to 4 relative to that of Comparative Example 1 is calculated, with the photoelectric conversion efficiency of Comparative Example 1 as the blank standard. The following can be seen.
[0181] The increase in PCE in Example 1 (26%) is significantly higher than the simple sum of the increase in PCE in Comparative Examples 4 and 6 (18% + 3% = 21%). The increase in PCE in Example 2 (28%) is significantly higher than the simple sum of the increase in PCE in Comparative Examples 2 and 5 (3% + 2% = 5%). The increase in PCE in Example 3 (31%) is significantly higher than the simple sum of the increase in PCE in Comparative Examples 3 and 7 (7% + 8% = 15%). The increase in PCE in Example 4 (32%) is significantly higher than the simple sum of the increase in PCE in Comparative Examples 4 and 8 (18 + 12% = 30%). The surfactant and the nitrogen-containing compound have an unexpected synergistic effect, which significantly improves the light absorption properties of the photoactive crystalline material layer, specifically, the penetration grain 313 occupancy rate p≧80 of the active crystalline material layer, and at the same time, the average flatness coefficient R avg ≦75, and a photovoltaic device with significantly improved energy conversion efficiency was obtained.
[0182] It should be explained that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is an example, and any embodiment having substantially the same configuration as the technical idea and having the same effect within the scope of the technical proposal of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other forms constructed by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application. [Explanation of symbols]
[0183] The base 106, the first electrode 105, the first charge transport layer 104, the photoactive crystalline material layer 103, the second charge transport layer 102, the second electrode 101, the through grain (313), the backlight grains (31, 32, 33), the width d of the backlight grains i , the protrusion height of the backlight grain h i , backlight surface 113, Incident light 151, reflected light 152, light receiving surface 112, grain boundary 325.
Claims
1. A photovoltaic device comprising a layer of photoactive crystalline material (103), the layer of photoactive crystalline material (103) comprising a first region; In the first region, the photoactive crystal material layer (103) comprises through grains (313), the through grains (313) being grains that pass through the photoactive crystal material layer (103), and the number of the through grains (313) is a percentage p≧80%, optionally p≧90%, of the total number of grains in the first region of the photoactive crystal material layer (103); and In the first region, the photoactive crystal material layer (103) includes a backlight side (113) and backlight crystal grains (31, 32, 33), at least one surface of the backlight crystal grains (31, 32, 33) is exposed to the backlight side (113), and the surface of the backlight crystal grains (31, 32, 33) exposed to the backlight side (113) is a backlight crystal surface; Here, the backlight side (113) has an average flatness coefficient R avg With R avg ≦75, and optionally 10≦R avg ≦70, Here, R on the backlight side (113) avg is calculated by the following formula: [0050] Here, R i is the flatness factor of the i-th backlight grain (31, 32, 33) in the first region, and R i is calculated by the following formula: R i =d i / h i Here, d i is the width of the backlight crystal plane of the i-th backlight crystal grain (31, 32, 33) in the first region, Here, h i is the protrusion height of the backlight crystal surface of the i-th backlight crystal grain (31, 32, 33) in the first region, wherein n is the number of all backlight grains (31, 32, 33) within said first region.
2. The photoactive crystalline material comprises an A / M / X crystalline material, the A / M / X crystalline material having the general formula: [A] a [M] b [X] c [M] comprises one or more first cations, the first cations comprising a metal ion, a metalloid ion, or a combination thereof; [A] contains one or more second cations, [X] contains one or more halogen anions, a is 1-6, optionally a is 1, 2, 3, 4, 5 or 6; b is 1-6; optionally, b is 1, 2, 3, 4, 5, or 6; 2. The photovoltaic device of claim 1, wherein c is 1 to 18; optionally, c is 3, 6, 9, or 18.
3. (1) The one or more first cations are Ca 2+ , Sr 2+ , Cd 2+ , Cu 2+ , Ni 2+ , Mn 2+、 Fe 2+ , Co 2+ , Pd 2+ , Ge 2+ , Sn 2+、 Pb 2+ , Yb 2+ , Eu 2+ , Bi3+, Sb3+, Pd 4+ , W 4+ , R 4+ , Os 4+ , Ir 4+ , Pt 4+ , Sn 4+ , Pb 4+ , Ge 4+ Or Te 4+ is selected from Optionally, the one or more first cations are Cu 2+ , Pb 2+ , Ge 2+ Or Sn 2+ and (2) The one or more second cations are Cs + , (NR 1 R 2 R 3 R 4 ) + , (R 1 R 2 N=CR 3 R 4 ) + , (R 1 R 2 N-C(R 5 ) = NR 3 R 4 ) + Or (R 1 R 2 N-C (N 5 R 6 ) = R 3 R 4 ) + where R 1 , R 2 , R 3 , R 4 , R 5 and R 6 each independently represents H, substituted or unsubstituted C 1-20 is selected from an alkyl group, or a substituted or unsubstituted aryl group; Optionally, the one or more second cations are Cs + , (CH 3 N.H. 3 ) + , (H 2 N-C(H)=NH 2 ) + and (3) The halogen anion is Cl - , B - Or I - The photovoltaic device of claim 2 , further comprising one or more of the following characteristics:
4. The A / M / X crystalline material is FAPbI 3 , FAPbBr 3 , FAPbCl 3 , FAPbF 3 , FAPbBr x I 3-x , FAPbBr x Cl 3-x , FAPbI x Br 3-x , FAPbI x Cl 3-x , FAPbCl x Br 3-x , FAPbI 3-x Cl x , CsPbI 3 , CsPbBr 3 , CsPbCl 3 , CsPbF 3 , CsPbBr x I 3-x , CsPbBr x Cl 3-x , CsPbI x Br 3-x , CsPbI x Cl 3-x , CsPbCl x Br 3-x , CsPbI 3-x Cl x , FA 1-y Cs y PbI 3 , FA 1-y Cs y PbBr 3 , FA 1-y Cs y PbCl 3 , FA 1-y Cs y PbF 3 , FA 1-y Cs y PbBr x I 3-x , FA 1-y Cs y PbBr x Cl 3-x , FA 1-y Cs y PbI x Br 3-x , FA 1-y Cs y PbI x C 3-x , F.A. 1-y Cs y PbCl x B 3-x , F.A. 1-y Cs y PbI 3-x C x or a combination thereof, 4. The photovoltaic device according to claim 2 or 3, wherein x = 0 to 3, and y = 0.01 to 0.
25.
5. The A / M / X crystal material is FAPbI 3 , CsPbI 3 , F.A. 1-y Cs y PbI 3 or a combination thereof, where y=0.01 to 0.
25.
6. 6. The photovoltaic device of any one of claims 2 to 5, wherein the layer of photoactive crystalline material has a thickness of at least 100 nm, optionally between 100 and 1000 nm, optionally between 300 and 700 nm.
7. further comprising a first charge transport layer (104) and a second charge transport layer (102), said photoactive crystalline material layer (103) being located between said first charge transport layer (104) and said second charge transport layer (102); the first charge transport layer (104) and the second charge transport layer (102) are an electron transport layer and a hole transport layer, respectively; or The photovoltaic device of any one of claims 1 to 6, wherein the first charge transport layer (104) and the second charge transport layer (102) are hole transport layers and electron transport layers, respectively.
8. further comprising a first electrode (105) and a second electrode (101), the electron transport layer, the hole transport layer and the photoactive crystalline material layer being located between the first electrode (105) and the second electrode (101); Optionally, the first electrode (105) comprises a transparent conductive oxide; 8. The photovoltaic device of claim 7, optionally wherein the second electrode (101) comprises a metal.
9. 1. A method for producing an A / M / X crystalline material, the A / M / X crystalline material having the general formula: [A] a [M] b [X] c [M] comprises one or more first cations, the first cations comprising a metal ion, a metalloid ion, or a combination thereof; [A] contains one or more second cations, [X] contains one or more halogen anions, a is 1 to 6, for example, a=1; b is 1 to 6, for example, b=1; c is 1 to 18, for example, c=3; The method includes disposing a precursor composition on a substrate, the precursor composition comprising: (a) at least one precursor compound; (b) a solvent; (c) a surfactant, and (d) A method for producing an A / M / X crystalline material that includes a component called an amino-based compound.
10. (1) The surfactant includes an amphoteric surfactant; (2) The method of claim 9, wherein the amino compound comprises one or more of a nitrile amine compound, an amino acid compound (e.g., a sulfamic acid compound), a hydrazine compound, a urea compound (e.g., urea, urea formaldehyde, biuret, triuret), a guanidine compound, or a salt or hydrate thereof.
11. 11. The method of claim 9 or 10, wherein the surfactant comprises dodecyl aminopropionate, dodecyl ethoxy sulfobetaine, dodecyl dimethyl hydroxypropyl sulfobetaine, zwitterionic polyacrylamide, octadecyl dihydroxyethylamine oxide, tetradecyl dihydroxyethylamine oxide, lauramidopropylamine oxide, dodecyl betaine, L-α-phosphatidylcholine, 3-(N,N-dimethyltetradecylammonium) propane sulfonate, dodecyl benzene sulfonate, or a combination thereof.
12. The amino compound is urea formaldehyde (C 3 H 8 N 2 O 3 ), isobutyraldehyde condensed urea (C 6 H 14 N 4 O 2 ), hydrazine (H 4 N 2 ), guanidine (CH 3 N 3 O), nitrile amines (CH 2 N 2 ), sulfamic acid (H 3 NO 3 S), or a combination thereof.
13. 13. The method of any one of claims 9 to 12, wherein the precursor composition comprises a first solvent and a second solvent, the first solvent having a boiling point of 40 to 165°C and the second solvent having a boiling point of 170 to 250°C.
14. (1) the first solvent is selected from one or more of N,N-dimethylformamide (DMF), 2-methoxyethanol, and acetonitrile (ACN); (2) the second solvent is selected from one or more of dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), and diphenyl sulfoxide (DPSO); (3) The method according to claim 13, wherein the volume ratio of the first solvent to the second solvent is (4-10):
1.
15. The precursor composition comprises: a first precursor compound containing a first cation; A method according to any one of claims 9 to 14, comprising a second precursor compound containing a second cation.
16. (1) the first precursor compound contains a halogen anion; and (2) the second precursor compound contains a halogen anion.
17. (1) The first precursor compound is lead iodide (PbI 2 ), lead bromide (PbBr 2 ), or a combination thereof; (2) the second precursor compound comprises one or more of formamidine hydroiodide (FAI), formamidine hydrobromide (FABr), cesium iodide (CsI), cesium bromide (CsBr), or combinations thereof.
18. The method further includes a step of performing a curing process on the precursor composition applied to the surface of the substrate, Optionally, the curing treatment comprises a vacuum treatment, an air knife treatment, an infrared light treatment or a combination thereof.
19. The method further comprises subjecting the cured product to an annealing treatment; Optionally, the temperature of the annealing treatment is between 100° C. and 170° C.; Optionally, the annealing treatment time is between 5 min and 60 min.
20. A method of manufacturing a photovoltaic device, the photovoltaic device comprising a first electrode (105), a second electrode (101), a first charge transport layer (104) and a second charge transport layer (102) located between the first electrode (105) and the second electrode (101), and an A / M / X crystalline material layer located between the first charge transport layer (104) and the second charge transport layer (102); The method comprises: Providing a first electrode (105) having a first charge transport layer (104) disposed on a surface thereof; forming a layer of the A / M / X crystalline material on a surface of the first charge transport layer (104) according to the method for producing the A / M / X crystalline material according to any one of claims 9 to 19; forming a second charge transport layer (102) on the layer of A / M / X crystalline material; forming a second electrode (101) on the second charge transport layer (102); wherein the first charge transport layer (104) and the second charge transport layer (102) are an electron transport layer and a hole transport layer, respectively; or A method of manufacturing a photovoltaic device, wherein the first charge transport layer (104) and the second charge transport layer (102) are a hole transport layer and an electron transport layer, respectively.
Citation Information
Patent Citations
Perovskite suspension state precursor solution and film forming method
CN111710784A
Preparation method and application of perovskite solar cell additive
CN113416155A
Thin film polycrystalline solar battery and formation method therefor
JP2002343993A
Mixed cation perovskite
JP2018536995A
Hybrid perovskite films
US20170098514A1